2001
DOI: 10.1002/ijc.1368
|View full text |Cite
|
Sign up to set email alerts
|

Role of HGF/c-met system in invasion and metastasis of oral squamous cell carcinoma cellsin vitro and its clinical significance

Abstract: We examined the role of the hepatocyte growth factor (HGF)/c-met system on invasion and metastasis of oral squamous cell carcinoma (SCC) cells. In monolayer culture, exogenous HGF marginally affected the growth of oral SCC cells (BHY, HN, IH) and human gingival epithelial cells (GE). In type I collagen matrix, however, HGF significantly enhanced the invasive growth of the cancer cells (p < 0.05). We detected the expression of c-met (HGF receptor) mRNA in all of the cancer cells, but not in human gingival fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 29 publications
2
62
0
6
Order By: Relevance
“…(4)(5)(6) It is also known to be a scatter factor (SF) (4) and involved in tumor-stromal interactions and EMT. (25,26) MET, a specific receptor tyrosine kinase for HGF ⁄ SF, is upregulated in various tumors including human HNSCC and its signal transduction induces progression and invasiveness of HNSCC in a paracrine or autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4)(5)(6) It is also known to be a scatter factor (SF) (4) and involved in tumor-stromal interactions and EMT. (25,26) MET, a specific receptor tyrosine kinase for HGF ⁄ SF, is upregulated in various tumors including human HNSCC and its signal transduction induces progression and invasiveness of HNSCC in a paracrine or autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…(25,26) MET, a specific receptor tyrosine kinase for HGF ⁄ SF, is upregulated in various tumors including human HNSCC and its signal transduction induces progression and invasiveness of HNSCC in a paracrine or autocrine manner. (5)(6)(7) Indeed, it has been reported that HGF ⁄ SF promotes cell migration and angiogenesis in human esophageal SCC, (27) upregulates the expression of proangiogenic cytokines interleukin (IL)-8 and vascular endothelial growth factor (VEGF) through the activation of mitogen-activated protein ⁄ extracellular signal-regulated kinase kinase (MEK) and phosphatidylinositol 3¢-kinase (PI3K) signaling pathways in HNSCC, (28) and induces the invasion of oral SCC by matrix metalloproteinase genes through the upregulation of the transcription factor E1AF. (29) However, how HGF ⁄ SF and MET signaling cascade affects the expression of each specific downstream functional gene has not yet been elucidated in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in disruption of intercellular junctions, dissolution of epithelial basement membrane and altered integrin interactions with extracellular matrix (Trusolino and Comoglio, 2002). Fibroblast-derived HGF/SF has been shown to stimulate invasion and migration in a number of tumour types including squamous cell carcinoma (Matsumoto et al, 1994;Uchida et al, 2001), and we have demonstrated previously that exogenous HGF/SF induces expression of the type IV collagenases MMP-2 and -9 in squamous carcinoma cells (Bennett et al, 2000). The latter observation suggests a possible mechanism for the HGF/SF-dependent invasion through basement membrane-like Matrigel (which comprises predominantly type IV collagen) described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al recently showed that a nonautocrine interaction between HGF transgenic hosts and c-Met expressing melanoma cells significantly promotes tumor metastasis in vivo (Yu and Merlino, 2002). Clinically, elevated serum HGF levels have been found in patients with cancers from bladder, breast, colon, gastric, liver, lung and head and neck (Takigawa et al, 1997;Taniguchi et al, 1997;Fukuura et al, 1998;Toi et al, 1998;Junbo et al, 1999;Gohji et al, 2000;Naughton et al, 2001;Uchida et al, 2001, Dong, 2001b. Significantly, this elevated serum HGF is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%